2021
DOI: 10.5187/jast.2021.e112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brown rice to replace corn in weanling pig diet

Abstract: This study was conducted to evaluate the effects of brown rice (Japonica) on growth performance, nutrient digestibility, and blood parameters of weanling pigs. A total of 60 weanling pigs (28-day-old, 30 barrows and 30 gilts, 6.73 ± 0.77 kg body weight [BW]) were randomly allotted to 2 dietary treatments (6 pigs per pen; 5 replicates per treatment) in a randomized complete block design with the initial BW and sex as blocks. The dietary treatments were a typical nursery diet based on corn and soybean meal (CON)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, it had a good effect on cost reduction and efficiency in animal production ( 23 ). Nevertheless, studies have shown that feeding weaned piglets with brown rice as a 50% substitute for corn resulted in an increase of 2.43 and 2.88% in apparent ileal digestibility of dry matter and energy compared to the control group, respectively ( 24 ). The reasons for the different results may be attributed to the different growth stages of the experimental animals selected by researchers, as well as the differences in the storage time of brown rice.…”
Section: Discussionmentioning
confidence: 99%
“…However, it had a good effect on cost reduction and efficiency in animal production ( 23 ). Nevertheless, studies have shown that feeding weaned piglets with brown rice as a 50% substitute for corn resulted in an increase of 2.43 and 2.88% in apparent ileal digestibility of dry matter and energy compared to the control group, respectively ( 24 ). The reasons for the different results may be attributed to the different growth stages of the experimental animals selected by researchers, as well as the differences in the storage time of brown rice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of fibrous diets may increase the thickness of the unstirred water layer adjacent to gut mucosa, leading to impaired nutrient utilization [24]. A previous study also demonstrated that a high fiber content might form a physical barrier to block enzymes' access to starch granules to restrain starch hydrolysis [25]. Moreover, increased dietary fiber is able to adsorb amino acids (AAs) and peptides, withholding them from digestion, and hence limiting AAs' availability for protein deposition in growing pigs [26].…”
Section: Discussionmentioning
confidence: 99%
“…in which the C 1 and C 2 are initial facilitation magnitudes, τ 1 and τ 2 are the fitted time constants. 42,43 The decay process can be divided into two coupling phases: a rapid phase with a short relaxation time constant (τ 1 = 33 ms) and a subsequent slow phase with a large time constant (τ 2 = 774 ms), [44][45][46] which are commensurate in scale with that observed in biological synapses. 47 We further demonstrate high-pass dynamics filtering using the STP properties of the device by applying multiple gate pulses with varying frequencies.…”
Section: Synaptic Characteristicsmentioning
confidence: 96%